Optimal Method for Allocation of Tractors and Trailers in Daily Dispatches of Road Drops and Pull Transport - Hao Chen; Wenxian Wang; Birong Cheng; Min Zhou (Journal of Advanced Transportation)
The domestic road drop and pull transportation system allows only tractors and semitrailers. In this mode, any tractors can only run with one semitrailer at a time or with no load. By optimizing the tractor scheduling plan, the no-load mileage of the tractor can be reduced, which can improve the efficiency and reduce the number of tractors. In this article, we have developed an optimization model for the tractor routing scheme to minimize the total cost of the drop and pull transportation system, which can limit the total number of tractors because the tractor can transport as many semitrailers to the destination as possible within the time window. Focusing on this mixed integer nonlinear problem, an improved ant search algorithm is designed. Finally, with Sichuan’s Anji Logistics Enterprise as the background, this tractor scheduling optimization model is applied to an ideal network and a real scenario. The results show that the optimized system reduces total cost by approximately18.7% and the ratio of tractors to semitrailers is approximately 1 : 3.31.